Diagnóstico e propostas para a gestão otimizada dos resíduos de saúde para os 50 municípios do Oeste do estado do Paraná - Pesibiczeski, Renato Augusto Marcon (2023)
Waste from health services has been growing in recent years and assuming great importance in the field of environmental management. The objective of this work was to make a diagnosis and present proposals for the optimized management of health waste for the 50 municipalities in the western state of Paraná. Of a quanti-qualitative nature, the work was developed in 6 stages, which are: 1) To characterize the sources of generation of Solid Waste in Health; 2) Qualitative and quantitative characterization of the sources generated from SSC; 3) Estimate the potential of daily, monthly and annual generation of SWH; 4) Prospect and propose new models of SWH management; 5) To analyze the feasibility of implementation and its impacts from the social, environmental, economic and public health point of view. As a result of the research, it was observed that the western region does not have an organized waste management, and almost half of these are sent out of state, without any treatment or income generation to improve the local economy. Also, a new management model was shown for the region, with emphasis on the segregation of SWH and the method of treatment by Pyrolysis, which is the most efficient. In relation to the management model based on the segregation at the origin of the materials used in health services, it was evidenced the need to develop a digital system (interface) that allows the explanation of the materials used in the packaging of the products used in health services.